Screen Traffic: Movies, Multiplexes, and Global Culture - Acland, Charles R. (Duke University Press, 2003)
A study of Hollywood, the internaitonal markets, and the way movies are actually shown in theaters.
https://katalog.adlr.link/Record/76-EBC1167926